Maximal inequalities in noncommutative probability spaces. Issue 2 (17th February 2022) - Sadeghi, Gh.; Moslehian, M. S.; Talebi, A.
Abstract : We employ some techniques involving projections in von Neumann algebras to establish some maximal inequalities such as the strong and weak symmetrization, Lévy, Lévy–Skorohod, and Ottaviani inequalities in the realm of noncommutative probability spaces. As consequence, we derive the corresponding inequalities in the commutative set-up.